OPTIMALISASI BEBAN KERJA DAN STANDARISASI ELEMEN KERJA UNTUK MENINGKATKAN EFISIENSI PROSES FINISHING PART OUTER DOOR DI PT TMMIN - Nurcahyo, Iswayudi Dwi; Hartono, Gunawarman (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
This research executes a working measurement or time study of each operator on three work stations in the finishing line. From the calculation, it is identified that workload of each operator is very low with an average efficiency of 28%. The number of operators can be optimized from nine to three people, so that work efficiency will increase to approximately 85%. To better see the potency of work element repair with no added value, Yamazumi loading chart is created. Meanwhile, to ensure that the process works, a work standardization of process flow diagrams and sequence of work, takt time, and cycle time is implemented, where the cycle time must be set after the proposed improvements are implemented.